Pengaruh Citra Merek dan Gaya Hidup terhadap Keputusan Pembelian Jilbab Rabbani pada Kalangan Siswa di SMP PGRI Brebes - Sri Ratih Handayani; Ulul Absor; Amsirun Amsirun (Sekolah Tinggi Ilmu Ekonomi Widya Manggalia, 2023)
ABSTRACTThis research uses quantitative methods. Quantitative method can be interpreted as a research method based on the philosophy of positivism, used to examine certain populations or samples, collecting data using research instruments, analyzing data is quantitative/statistical, with the aim of testing established hypotheses. (Sugiyono, 2018:35-36). Based on the analysis of research data carried out by the author, the following results were obtained:1. Partial hypothesis testing (statistical t test) showed that the brand image variable (X1) and lifestyle variable (X2) partially had a significant positive effect on the purchasing decision variable (Y) Rabbani hijab among students at SMP PGRI Brebes.2. Simultaneous hypothesis testing (F statistical test) showed that the brand image variable (X1) and lifestyle variable (X2) together had a positive and significant effect on the purchase decision variable (Y) Rabbani hijab among students at SMP PGRI Brebes .3. Testing regression analysis of brand image and lifestyle variables onpurchasing decisions Y = 10.346 + 0.472X1 + 0.328X2 + e. From the testresults, it was found that brand image (X1) had a more dominant effect with a regression coefficient of 0.472 on purchasing decisions (Y) for Rabbani headscarves among students at SMP PGRI Brebes. Keywords: Brand Image, Lifestyle and Purchase Decisions